Status of Safety Provision in Science Laboratories at Secondary Level - Ullah Khan, Irfan (JSE, 2025)
The study was carried out to determine the status of safety provision in science laboratories in government high schools for boys at secondary level in district Lakki Marwat by assessing the availability and functionality of safety equipment according to the required quantity. A descriptive survey research design was adopted in carrying out the study. The population of the study consisted of science laboratories in all the 62 government high schools for boys in district Lakki Marwat. A total of 46 government high schools for boys were selected randomly to make sample of the study. A validated and reliable check list was used to observe the availability and functionality of essential safety equipment according to the required quantity in science laboratories of government high schools for boys included in sample. The data collected through checklist were analyzed using frequency counts and percentages. The major findings of the study were; safety provision was totally ignored in the laboratories; majority of the laboratories did not possess the required quantity of acid cabinets, fire extinguishers, and first aid kits. Moreover, no laboratory possessed eye wash station, fire blankets, fire proof cupboards, gas masks, hand gloves, laboratory coats and safety goggles according to the required quantity. It was recommended that laboratories should be made well equipped in respect of safety equipment. Moreover, immediate reforms in policy, budgeting training, and monitoring should be ensured to provide safety provision in schools at the secondary level